Ethical Issues related to End of Life Treatment in Patients with Advanced Dementia – The Case of Artificial Nutrition and Hydration (Diametros, 2016)
Patients with advanced dementia suffer from severe cognitive and functional impairment, including eating disorders. The focus of our research is on the issue of life-sustaining treatment, specifically on the social and ethical implications of tube feeding. The treatment decision, based on values of life and dignity, involves sustaining lives that many people consider not worth living. We explore the moral approach to caring for these patients and review the history of the debate on artificial nutrition and hydration showing the impact of the varying perceptions of the value of these patients' lives on changing norms. We argue that in light of the value of solidarity, decisions about life-sustaining treatment for patients with advanced dementia should be made on a case by case basis, as with any other patient, in consideration of the medical implications of the intervention which might best serve the goals of care for the individual patient.
Keywords: artificial nutrition and hydration; comfort feeding; dementia; dignity; end of life; ethics; solidarity; tube feeding; right to life